2016
DOI: 10.1016/j.ophtha.2016.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Reflective Drusen Substructures Predict Progression to Geographic Atrophy in Age-related Macular Degeneration

Abstract: Purpose Structural and compositional heterogeneity within drusen, composed of lipid, carbohydrates, and proteins, have been previously described. We sought to detect and define phenotypic patterns of drusen heterogeneity in the form of optical coherence tomography–reflective drusen substructures (ODS) and examine their associations with age-related macular degeneration (AMD)-related features and AMD progression. Design Retrospective analysis in a prospective study. Participants Patients with intermediate A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 38 publications
0
77
1
Order By: Relevance
“…29 A better classification that becomes widely established would be also helpful for interpretation of other potential precursor lesions that have been recently described by SD-OCT, such as thinning of retinal layers in the presence of drusen regression, evolution of HRF, and disintegrated RPE dots. 23,[26][27][28][47][48][49][50][51] Various limitations of this study need to be considered. The number of included subjects is relatively small, and a substantial high number of subjects dropped out of this natural history study (a total of 32.7% at year 6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 A better classification that becomes widely established would be also helpful for interpretation of other potential precursor lesions that have been recently described by SD-OCT, such as thinning of retinal layers in the presence of drusen regression, evolution of HRF, and disintegrated RPE dots. 23,[26][27][28][47][48][49][50][51] Various limitations of this study need to be considered. The number of included subjects is relatively small, and a substantial high number of subjects dropped out of this natural history study (a total of 32.7% at year 6).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Age-Related Eye Disease studies (AREDS 1 and AREDS 2) have reported the development of atrophy based on definitions by CFP in eyes with early and intermediate AMD (iAMD). 21,23 While CFP assessment has been established as the gold standard in clinical AMD trials, the ability to detect early stages of atrophy and precursor lesions is challenging due to low contrast and limited resolution. 24 Using high-resolution multimodal imaging, in particular spectral-domain optical coherence tomography (SD-OCT) and confocal scanning laser ophthalmoscopy (cSLO) fundus autofluorescence (FAF), the evolution of atrophy has been scrutinized in more detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 In the intermediate stage of AMD, various drusen-related patterns of reflectivity on SDOCT have been discovered, 814 and found to be early indicators of advancing disease. 1421 It had been unknown if such SDOCT features implied a risk of progression to choroidal neovascularization or played a role in the sequence of degeneration in geographic atrophy (GA). Previous reports from the A2A SDOCT Study discovered features of intermediate AMD on SDOCT that can serve as biomarkers of disease progression, such as hyperreflective foci (HF).…”
mentioning
confidence: 99%
“…Previous reports from the A2A SDOCT Study discovered features of intermediate AMD on SDOCT that can serve as biomarkers of disease progression, such as hyperreflective foci (HF). 14,1821 Incidence of new-onset GA on CP followed after the qualitative SDOCT findings of atypical drusen (i.e. high or low internal reflectivity) 12 , OCT-reflective drusen substructures (ODS, i.e.…”
mentioning
confidence: 99%